Effect of IV Infusion of Magnesium Sulfate on Postoperative Pain after Spinal Anesthesia: A Prospective Randomized Trial - Shubhi Singhal (Tehran University of Medical Sciences, 2021)
Background: The current study attempts to evaluate the effect of intravenous (IV) infusion of magnesium sulfate during spinal anesthesia on postoperative pain and postoperative analgesic requirements in lower limb surgeries. Methods: In this double blind, randomized controlled study, 60 patients undergoing elective lower limb surgeries, were selected and randomly divided into two groups. Group I received isotonic saline and group II was administered magnesium sulfate 50 mg Kg-1 IV for 15 min and then 15 mg Kg-1 h-1 by continuous IV infusion till the end of surgery or 2 hours, whichever was earlier. Ramsay sedation scores, VAS scores for pain, time of first administration of rescue analgesic and total analgesic requirement were noted in both the groups. Results: Statistically significant difference was observed in the VAS score between the two groups at 1st, 2nd, 3rd, 6th, 9th and 12th hour intervals; with VAS scores being lower in the magnesium group (p<0.05). The mean time of first rescue analgesic requirement in control group was 144.00 mins, while in magnesium group was 246.00 mins (p<0.05). The total rescue analgesic requirement was found to be 251.67 mg and 181.67 mg at the end of 24 hours, in control and magnesium groups, respectively (p<0.05). Conclusion: This study demonstrates statistically significant lowering of postoperative VAS scores, delayed need of postoperative analgesia and reduced total postoperative analgesic requirement in patients receiving intraoperative IV magnesium sulfate compared to the control group. Magnesium sulfate did not cause sedation or any other significant adverse effect in the doses used in the study.